Standberg type polyoxometallate-based organic-inorganic compound for catalytic oxidation desulfurization as well as synthesis method and application of Standberg type polyoxometallate-based organic-inorganic compound

By designing a Standberg polyoxylate-based organic-inorganic compound, the problem of insufficient oxidation capacity of existing oxidation desulfurization technology under low temperature conditions is solved, efficient catalytic oxidation and desulfurization is achieved, and the good reusability of the catalyst is demonstrated. .

CN119431410AActive Publication Date: 2025-02-14LIAONING UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411562290.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing oxidation and desulfurization technology has weak oxidation capacity under low temperature conditions, making it difficult to achieve efficient sulfide oxidation, especially when using H2O2 as an oxidant, it requires auxiliary catalysts.

Method used

Design and develop a Standberg polyoxylate-based organic-inorganic compound, which is adjusted by the ratio of zinc acetate, 3,5-diamino-1,2,4-triazole and sodium molybdate at room temperature. The catalyst is synthesized to form a one-dimensional chain structure and a three-dimensional supramolecular network structure, with high crystallinity and structural stability.

Benefits of technology

It achieves efficient catalytic oxidation and desulfurization under low temperature conditions, has strong catalytic performance, and the catalyst can be reused to maintain high catalytic efficiency. It is suitable for selective oxidation of various sulfide ethers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431410A_ABST
    Figure CN119431410A_ABST
Patent Text Reader

Abstract

The invention discloses a Standberg type polyoxometallate-based organic-inorganic compound for catalytic oxidation desulfurization as well as a synthesis method and application of the Standberg type polyoxometallate-based organic-inorganic compound. The molecular formula of the Standberg type polyoxometallate-based organic-inorganic compound is [Zn (H2datrz) 2 (P2Mo5O23) (H2O) 2]. 11H2O. The synthesis method comprises the following steps: step 1, mixing zinc acetate, 3, 5-diamino-1, 2, 4-triazole, sodium molybdate and deionized water to a homogeneous phase; the molar ratio of the zinc acetate to the deionized water is 1: 173, the molar ratio of the 3, 5-diamino-1, 2, 4-triazole to the sodium molybdate is 1: 1, and the molar ratio of the 3, 5-diamino-1, 2, 4-triazole to the zinc acetate is 4: 3; 2, adjusting the pH value to 2.5-3, stirring, heating, and carrying out hot filtration; and 3, standing the filtrate at room temperature for one week to obtain a product. The method has the characteristics of low cost, high yield and high catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic catalysis and synthesis methods, and more specifically, to a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization and a synthesis method thereof. Background Art

[0002] Research on sulfide oxidation reactions has always attracted much attention. On the one hand, the oxidation products of sulfide, sulfoxide and sulfone, are widely used in fine chemicals such as medicine and pesticides, while sulfone and sulfoxide are important synthetic intermediates in organic synthesis reactions and have broad application prospects in reactions such as synthetic functional materials and molecular recombination. On the other hand, sulfide, as the main source of sulfur, is widely present in fuels such as diesel and gasoline. During high-temperature combustion, sulfide will be converted into SO x , leading to the formation of acid rain and acid mist, causing harm to the environment and human health.

[0003] With the improvement of global environmental awareness, the development of efficient fuel desulfurization technology has become a research hotspot. Oxidative desulfurization technology has attracted widespread attention due to its advantages such as low cost, high desulfurization efficiency, and good product selectivity. However, its disadvantage is that hydrogen peroxide (H 2 O 2 ), molecular oxygen and tert-butyl hydroperoxide have weak oxidizing abilities, especially at low temperatures, and it is difficult to achieve a good oxidation effect, so that the reaction system needs the assistance of a catalyst to complete the oxidation reaction. Therefore, when using H 2 O 2 In order to realize green oxidation process as oxidant, it is necessary to establish a more efficient catalytic system.

[0004] Polyoxometalates (POMs), as inorganic metal oxide clusters with clear structures and remarkable physicochemical properties, are widely used in catalysis, optics, magnetism, electrochemistry, medicine and other fields. In particular, their excellent thermal stability, compatibility with various oxidants and unique redox behavior make them ideal catalysts for thioether conversion. Summary of the invention

[0005] The purpose of the present invention is to design and develop a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which has high crystallinity and good structural stability.

[0006] The present invention also designs and develops a method for synthesizing a Standberg-type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which can be synthesized at room temperature by adjusting the ratio of zinc acetate, 3,5-diamino-1,2,4-triazole and sodium molybdate, and has a high synthesis yield.

[0007] The present invention also designs and develops an application of a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which has stronger catalytic performance and can be reused.

[0008] The technical solution provided by the present invention is:

[0009] A Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, wherein the molecular formula of the Standberg type polyoxometalate-based organic-inorganic compound is [Zn(H 2 datrz) 2 (P 2 Mo 5 O 23 )(H 2 O) 2 ]·11H 2 O;

[0010] Among them, Hdatrz is 3,5-diamino-1,2,4-triazole. Since Hdatrz is protonated in the Standberg type polyoxometalate-based organic-inorganic compound, H 2 datrz is the protonated H 2 datrz cation.

[0011] A method for synthesizing a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization comprises the following steps:

[0012] Step 1: Mix zinc acetate, 3,5-diamino-1,2,4-triazole, sodium molybdate and deionized water until they are homogeneous;

[0013] Wherein, the molar ratio of zinc acetate to deionized water is 1:173, the molar ratio of 3,5-diamino-1,2,4-triazole to sodium molybdate is 1:1, and the molar ratio of 3,5-diamino-1,2,4-triazole to zinc acetate is 4:3;

[0014] Step 2: Adjust the pH value of the mixed solution to 2.5, heat to 95°C for 2 hours after stirring, and filter hot;

[0015] Step 3: Allow the filtrate to stand at room temperature for one week to obtain a Standberg-type polyoxometalate-based organic-inorganic compound.

[0016] Preferably, the zinc acetate is (CH 3 COO 2 Zn·2H 2 O, the sodium molybdate is Na 2 MoO 4 ·2H2 O.

[0017] Preferably, in step 2, 85% H 3 PO 4 Perform pH adjustment.

[0018] Preferably, the stirring time in step 2 is 30 minutes.

[0019] Preferably, the heating rate in step 2 is 15° C. / h.

[0020] Preferably, the container needs to be sealed during the heating process in step 2.

[0021] Preferably, the Standberg type polyoxometalate-based organic-inorganic compound is a yellow block crystal.

[0022] Preferably, it also includes:

[0023] The obtained yellow block crystals were washed 2 to 4 times with deionized water.

[0024] Disclosed is an application of a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, a Standberg type polyoxometalate-based organic-inorganic compound synthesized using the synthesis method of the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, and an application of the Standberg type polyoxometalate-based organic-inorganic compound in catalysis of selective oxidation of thioethers.

[0025] The beneficial effects of the present invention are:

[0026] (1) The present invention designs and develops a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which is composed of a protonated H2datrz cation, a Standberg type [P 2 Mo 5 O 23 ] 6- Anions and central zinc metal ions form a one-dimensional (1D) infinitely extended chain structure. These 1D chain structures are further assembled into a three-dimensional (3D) supramolecular network structure through multiple hydrogen bond interactions, which has high crystallinity and good structural stability.

[0027] (2) The method for synthesizing the Standberg-type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization designed and developed by the present invention is simple, fast, has a short synthesis cycle, a high synthesis yield, and a low synthesis cost.

[0028] (3) The present invention designs and develops a Standberg-type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which is easy to separate from the reaction medium and does not pollute the reaction products. It has stronger catalytic performance and can be reused in subsequent cycle reactions while still maintaining a high catalytic efficiency. At the same time, due to the unique structural characteristics of the compound, the compound has the potential to become a new catalyst for the selective oxidation reaction of thioethers, opening up a new direction for related research. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the coordination environment diagram of the compound described in the present invention.

[0030] Figure 2 [P 2 Mo 5 O 23 ] 6- Structural diagram.

[0031] Figure 3 It is a 1D chain structure diagram of the compound described in the present invention.

[0032] Figure 4 This is an infrared spectrum of the Standberg type polyoxometalate-based organic-inorganic compound used for catalytic oxidative desulfurization according to the present invention.

[0033] Figure 5 This is the X-ray powder diffraction pattern of the Standberg type polyoxometalate-based organic-inorganic compound used for catalytic oxidative desulfurization according to the present invention.

[0034] Figure 6 This is an infrared spectrum of the sample recovery after the product of the embodiment of the present invention and thioanisole were catalytically oxidized three times.

[0035] Figure 7 This is an X-ray powder diffraction pattern of the sample after the catalytic oxidation of the product of the embodiment of the present invention and p-thioanisole was repeated three times. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below so that those skilled in the art can implement it according to the description.

[0037] like Figure 1-Figure 3 As shown, the present invention provides a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, the molecular formula of which is [Zn(H 2 datrz) 2 (P 2 Mo 5 O 23)(H 2 O) 2 ]·11H 2 O;

[0038] Among them, Hdatrz is 3,5-diamino-1,2,4-triazole, and the structural formula is

[0039]

[0040] Since Hdatrz is protonated in Standberg-type polyoxometalate-based organic-inorganic compounds, H 2 datrz is the protonated H 2 datrz cation.

[0041] The invention designs and develops a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which comprises a protonated H2datrz cation, a Standberg type [P 2 Mo 5 O 23 ] 6- Anions and central zinc metal ions form a one-dimensional (1D) infinitely extended chain structure. These 1D chain structures are further assembled into a three-dimensional (3D) supramolecular network structure through multiple hydrogen bond interactions, which has high crystallinity and good structural stability.

[0042] The present invention also provides a method for synthesizing a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, comprising the following steps:

[0043] Step 1: Mix zinc acetate, 3,5-diamino-1,2,4-triazole, sodium molybdate and deionized water until they are homogeneous;

[0044] Wherein, the zinc acetate is (CH 3 COO 2 Zn·2H 2 O, the sodium molybdate is Na 2 MoO 4 ·2H 2 O, the molar ratio of zinc acetate to deionized water is 1:173, the molar ratio of 3,5-diamino-1,2,4-triazole to sodium molybdate is 1:1, and the molar ratio of 3,5-diamino-1,2,4-triazole to zinc acetate is 4:3;

[0045] Step 2: Adjust the pH value of the mixed solution to 2.5, heat to 95°C for 2 hours after stirring, and filter hot;

[0046] In this example, 85% H 3PO 4 The pH value was adjusted, the stirring time was 30 minutes, and the heating rate was 15°C / h;

[0047] In this embodiment, the heating process requires the beaker to be sealed;

[0048] Step 3, the filtrate is allowed to stand at room temperature for one week to obtain a Standberg type polyoxometalate-based organic-inorganic compound;

[0049] The filtrate obtained after hot filtration needs to be kept undisturbed for one week at room temperature;

[0050] The Standberg type polyoxometalate-based organic-inorganic compound is a yellow block crystal, and after obtaining the yellow block crystal, it needs to be washed with deionized water for 2 to 4 times.

[0051] Example

[0052] 2mmol Na 2 MoO 4 .2H 2 O, 1.5mmol(CH 3 COO 2 Zn·2H 2 O and 2 mmol Hdatrz were added to a beaker containing 20 mL of deionized water, stirred until homogeneous, and then 85% H 3 PO 4 The pH was adjusted to 2.5, stirred for 30 minutes, and then heated to 95°C at a rate of 15°C / h and maintained for 2 hours. After hot filtration, the filtrate was kept undisturbed at room temperature for one week to finally obtain yellow block crystals with a yield of about 40% (based on metal Mo).

[0053] like Figure 1 As shown in the figure, it is the coordination environment diagram of the compound, where Figure 2 As shown, [P 2 Mo 5 O 23 ] 6- The anion can be considered to be composed of the following two parts, namely, five MoO 6 Octahedrons are assembled into a ring structure by sharing one corner and six edges, and the two PO caps on both sides of the ring 4 Tetrahedron, such as Figure 3 As shown, adjacent [P 2 Mo 5 O 23 ] 6-The anion is further bridged by zinc ions to form a 1D chain structure, in which the zinc ion presents an octahedral coordination configuration, respectively with the two nitrogen atoms on the ligand, [P 2 Mo 5 O 23 ] 6- The two oxygen atoms on the anion are connected to two coordinated water molecules.

[0054] In another embodiment, changing the ratio of synthetic raw materials will cause the synthesized compound to be impure or unable to be synthesized, that is, when the ratio of synthetic raw materials is close to that described in the present invention, the compound is impure, and when the ratio of synthetic raw materials changes too much, it will lead to the inability to synthesize.

[0055] The compounds obtained in the examples are characterized:

[0056] 1. Infrared spectroscopy characterization of phase composition:

[0057] The infrared spectrum of the test compound material is carried out in the FT-IR spectrometer, such as Figure 4 As shown, the compounds have peaks at 3332 and 3142 cm -1 The absorption peaks at and are attributed to the OH stretching vibration of water molecules and the N-stretching vibration of the exocyclic amino group in the Hdatrz ligand. In the low wave number region, the Strandberg type [P 2 Mo 5 O 23 ] 6- The absorption peak is located at 1039 cm -1 and 1009cm -1 In addition, the absorption peak of Mo-O appears at 959 cm -1 and 890cm -1 , while the absorption peak of Mo-O-Mo is distributed at 557cm -1 ~793cm -1 .

[0058] 2. Powder diffraction characterization of phase purity:

[0059] The powder diffraction data were collected on a Rigaku Ultima IV X-ray diffractometer with an operating current of 40 mA, a voltage of 40 kV, a molybdenum target X-ray, fixed scanning, a receiving slit width of 0.1 mm, and a density data collection scanning range of 5° to 50°. The scanning speed was 5° / s, the span was 0.02° / time, and the single crystal structure powder diffraction spectrum simulation conversion used Mercury 1.4.1.

[0060] like Figure 5As shown, the powder X-ray diffraction spectrum of the compound is substantially consistent with the fitting spectrum, indicating that the Standberg type polyoxometalate-based organic-inorganic compound obtained in the embodiment of the present invention is pure phase and has high crystallinity.

[0061] 3. Crystal structure determination:

[0062] Single crystals of appropriate size were selected using a microscope, and diffraction data were collected at room temperature using a Bruker SMART APEX II diffractometer (graphite monochromator, Mo Kα (λ = 0.071073 nm). The scanning ω-θ diffraction data were subjected to absorption correction using the SADABS program. Data restoration and structural analysis were completed using the direct method and SHELX program, respectively. The ShelXL program for least squares minimization was used for optimization. Figure 1-Figure 3 The crystal structure of the compound synthesized in the example is shown, and its detailed crystallographic diffraction point data are shown in Table 1.

[0063] Table 1 Detailed crystallographic diffraction point data of compounds in the examples

[0064]

[0065]

[0066] The invention discloses a method for synthesizing a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which is simple, fast, has a short synthesis cycle, a high synthesis yield and a low synthesis cost.

[0067] The present invention also provides an application of a Standberg-type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, which can be used as a catalyst for the selective oxidation of sulfides. The catalyst is not only suitable for the selective oxidation of thioanisole, but can also effectively catalyze the selective oxidation of substrates such as 4-bromothioanisole, 4-chlorothioanisole, diphenyl disulfide and 2-chloroethyl ethyl sulfide, showing excellent catalytic performance.

[0068] The compound obtained in the example was used for selective catalytic oxidation of sulfide compounds (main product: sulfoxide), wherein the molar ratio of the catalyst to the sulfide compound was 0.021:1:

[0069] 1. Catalytic oxidation of thioanisole:

[0070] The compound obtained in the example was used as a catalyst, 0.4 mmol of thioanisole, 10 μmol of a polyacid-based organic-inorganic compound, 0.42 mmol of hydrogen peroxide (oxidant) and 5 mL of methanol solvent were put into a brown glass bottle, the reaction temperature was controlled at room temperature 25°C, and the reaction was stopped after stirring for 20 minutes.

[0071] 2. Catalytic oxidation of 4-chlorothioanisole:

[0072] The compound obtained in the example was used as a catalyst, 0.4 mmol 4-chlorothioanisole, 10 μmol polyacid-based organic-inorganic compound, 0.42 mmol hydrogen peroxide and 5 mL methanol solvent were put into a brown glass bottle, the reaction temperature was controlled at room temperature 25°C, and the reaction was stopped after stirring for 20 minutes.

[0073] 3. Catalytic oxidation of 4-bromothioanisole:

[0074] The compound obtained in the example was used as a catalyst, 0.4 mmol 4-bromoanisole, 10 μmol polyacid-based organic-inorganic compound, 0.42 mmol hydrogen peroxide and 5 mL methanol solvent were put into a brown glass bottle, the reaction temperature was controlled at room temperature 25°C, and the reaction was stopped after stirring for 20 minutes.

[0075] 4. Catalytic oxidation of diphenyl disulfide:

[0076] The compound obtained in the example was used as a catalyst, 0.4 mmol of diphenyl disulfide, 10 μmol of a polyacid-based organic-inorganic compound, 0.42 mmol of hydrogen peroxide and 5 mL of methanol solvent were put into a brown glass bottle, the reaction temperature was controlled at room temperature 25°C, and the reaction was stopped after stirring for 20 minutes.

[0077] 5. Catalytic oxidation of dibenzyl sulfide:

[0078] The compound obtained in the example was used as a catalyst, 0.4 mmol of dibenzyl sulfide, 10 μmol of a polyacid-based organic-inorganic compound, 0.42 mmol of hydrogen peroxide and 5 mL of a methanol solvent were put into a brown glass bottle, the reaction temperature was controlled at room temperature 25°C, and the reaction was stopped after stirring for 20 minutes.

[0079] 6. Catalytic oxidation of diethyl sulfide:

[0080] The compound obtained in the example was used as a catalyst, 0.4 mmol of diethyl sulfide, 10 μmol of a polyacid-based organic-inorganic compound, 0.42 mmol of hydrogen peroxide and 5 mL of methanol solvent were put into a brown glass bottle, the reaction temperature was controlled at room temperature 25°C, and the reaction was stopped after stirring for 20 minutes.

[0081] The samples were prepared for GC-MS detection, with naphthalene as the internal standard. The conversion rate and selectivity were calculated based on the results of GC-MS. The conversion rate of catalytic oxidation of sulfide compounds was expressed as:

[0082]

[0083] The selectivity of catalytic oxidation of sulfide compounds is expressed as:

[0084]

[0085] The reaction equation for the catalytic oxidation of sulfide compounds is expressed as:

[0086]

[0087] In the catalytic oxidation of thioanisole by the compound obtained in the example, the GC-MS result showed that the conversion rate of the oxidation of the reaction substrate to the corresponding sulfoxide was 99% and the selectivity was 96%; in the catalytic oxidation of 4-chlorothioanisole by the compound obtained in the example, the GC-MS result showed that the conversion rate of the oxidation of the reaction substrate to the corresponding sulfoxide was 99% and the selectivity was 91%; in the catalytic oxidation of 4-bromothioanisole by the compound obtained in the example, the GC-MS result showed that the conversion rate of the oxidation of the reaction substrate to the corresponding sulfoxide was 98% and the selectivity was 90%; in the catalytic oxidation of diphenyl disulfide by the compound obtained in the example, the GC-MS result showed that the conversion rate of the oxidation of the reaction substrate to the corresponding sulfoxide was 97% and the selectivity was 92%; in the catalytic oxidation of dibenzyl sulfide by the compound obtained in the example, the GC-MS result showed that the conversion rate of the oxidation of the reaction substrate to the corresponding sulfoxide was 98% and the selectivity was 93%; in the catalytic oxidation of diethyl sulfide by the compound obtained in the example, the GC-MS result showed that the conversion rate of the oxidation of the reaction substrate to the corresponding sulfoxide was 99% and the selectivity was 93%.

[0088] After the catalytic reaction of thioanisole with the compound obtained in the embodiment is completed, the compound is recycled and reused. The recycling method is as follows: after the reaction is completed, the obtained solution is filtered to filter out the polyacid-based organic-inorganic compound, and the compound is recycled after treatment. The recycled compound is used again for the catalytic oxidation reaction of sulfide compounds. After the first recycling, the compound is reused. GC-MS analysis shows that the conversion rate of thioanisole is 96% and the selectivity is 94%. After the catalyst is repeatedly recycled and used three times, GC-MS analysis shows that the conversion rate of thioanisole is greater than 95% and the selectivity is 94%. It can be seen that the catalytic effect has not been significantly weakened. Figure 6-Figure 7 As shown, the sample was recovered after three repetitions and subjected to infrared and powder diffraction characterization tests, which were in good agreement with the original infrared spectrum and powder diffraction spectrum, indicating that the polyacid-based organic-inorganic compound had good stability during the catalytic process.

[0089] The present invention designs and develops the application of Standberg type polyoxometalate-based organic-inorganic compounds for catalytic oxidation desulfurization. The polyoxometalate-based organic-inorganic compounds can always carry out the selective catalytic oxidation reaction of sulfide compounds at room temperature of 25°C, and have good catalytic ability, fast catalytic speed, high conversion rate and good selectivity.

[0090] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, characterized in that: The molecular formula of the Standberg type polyoxometalate-based organic-inorganic compound is [Zn(H2datrz)2(P2Mo5O 23 )(H2O)2]·11H2O; Here, Hdatrz is 3,5-diamino-1,2,4-triazole, and since Hdatrz is protonated in the Standberg type polyoxometalate-based organic-inorganic compound, H2datrz is a protonated H2datrz cation.

2. A method for synthesizing a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, characterized in that: The steps include: Step 1: Mix zinc acetate, 3,5-diamino-1,2,4-triazole, sodium molybdate and deionized water until they are homogeneous; Wherein, the molar ratio of zinc acetate to deionized water is 1:173, the molar ratio of 3,5-diamino-1,2,4-triazole to sodium molybdate is 1:1, and the molar ratio of 3,5-diamino-1,2,4-triazole to zinc acetate is 4:3; Step 2: Adjust the pH value of the mixed solution to 2.5, heat to 95°C for 2 hours after stirring, and filter hot; Step 3: Allow the filtrate to stand at room temperature for one week to obtain a Standberg-type polyoxometalate-based organic-inorganic compound.

3. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 2, characterized in that: The zinc acetate is (CH3COO)2Zn·2H2O, and the sodium molybdate is Na2MoO4·2H2O.

4. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 3, characterized in that: In the step 2, the pH value is adjusted by using 85% H3PO4.

5. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 4, characterized in that: The stirring time in step 2 is 30 minutes.

6. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 5, characterized in that: The heating rate in step 2 is 15° C. / h.

7. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 6, characterized in that: The sealing must be maintained during the heating process in step 2.

8. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 7, characterized in that: The Standberg type polyoxometalate-based organic-inorganic compound is a yellow block crystal.

9. The method for synthesizing the Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization according to claim 8, characterized in that: Also includes: The obtained yellow block crystals were washed 2 to 4 times with deionized water.

10. An application of a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization, wherein the Standberg type polyoxometalate-based organic-inorganic compound is synthesized by the method for synthesizing a Standberg type polyoxometalate-based organic-inorganic compound for catalytic oxidative desulfurization as claimed in any one of claims 2 to 9, characterized in that: The Standberg type polyoxometalate-based organic-inorganic compound is used in the catalysis of the selective oxidation of thioethers.

Citation Information

Patent Citations

  • Temperature-controlled polyoxometalate oxidative desulfurization catalyst and synthetic method thereof

    CN109967126A

  • Three-dimensional polyacid-based nickel metal-organic crystalline catalytic material and preparation method thereof

    CN110026241A

  • Waugh type polyoxometallate-based metal-organic complex for efficient catalytic oxidation desulfurization and application of Waugh type polyoxometallate-based metal-organic complex

    CN113527697A

  • Multi-acid-group supramolecular complex for normal-temperature catalytic oxidation desulfurization of thioether compounds and application of multi-acid-group supramolecular complex

    CN114989440A